Visualization of turbulent spots and unsteady wake-induced boundary-layer transition with thermochromic liquid crystals - Zhong, S; Kittichaikan, C; Hodson, H; Ireland, P (Elsevier, 1999)
A method of using thermochromic liquid crystals has been developed to visualize the thermal footprints of turbulent spots convecting downstream in an otherwise laminar boundary layer over a heated surface. This technique has been employed to visualize the development of turbulent spots under the influence of adverse pressure gradients. It has also been used to visualize the transitional events that occur during unsteady wake-induced boundary layer transition typically of those occurring in multi-stage turbomachines. The results show that liquid crystal is not only capable of providing quantitative information about the growth and development of individual spots but also allows a detailed study of formation of turbulent spots occurring naturally during a complicated transition process.